After the roundup : escape and survival in Hitler's France - Weismann, Joseph (Indiana University Press, 2017)
On the nights of July 16 and 17, 1942, French police rounded up eleven-year-old Joseph Weismann, his family, and 13,000 other Jews. After being held for five days in appalling conditions in the Vlodrome d'Hiver stadium, Joseph and his family were transported by cattle car to the Beaune-la-Rolande internment camp and brutally separated: all the adults and most of the children were transported on to Auschwitz and certain death, but 1,000 children were left behind to wait for a later train. The French guards told the children left behind that they would soon be reunited with their parents, but Joseph and his new friend, Joe Kogan, chose to risk everything in a daring escape attempt. After eluding the guards and crawling under razor-sharp barbed wire, Joseph found freedom. But how would he survive the rest of the war in Nazi-occupied France and build a life for himself? His problems had just begun. Until he was 80, Joseph Weismann kept his story to himself, giving only the slightest.